The Routledge diaspora studies reader - Wilson, Janet, 1948-; Stierstorfer, Klaus (Milton Park, Abingdon, Oxon ; New York, NY: Routledge, 2018)
"The Routledge Diaspora Studies Reader provides a comprehensive resource for students and scholars working in this vital interdisciplinary field. The book traces the emergence and development of Diaspora Studies as a field of scholarship, presenting key critical essays alongside more recent criticism that explores new directions. It also includes seminal essays that have been updated specifically for this collection, as well as brand new papers. The volume presents: substantial introductions to each section that situate each work within its historical, disciplinary and theoretical contexts essays grouped by key subject areas including Nation, Globalization, Postcolonialism, Race and Ethnicity, Multiculturalism, Intersectionality, Gender and Sexuality, Home and Belonging, Spaces, Hybridity, Religion, Literature, Visual Culture, and Digital Media writings by major figures including Robin Cohen, Homi Bhabha, Avtar Brah, Khachig Tölölyan, Pnina Werbner, Vijay Mishra, Paul Gilroy, Salman Rushdie, Stuart Hall, and Arjun Appadurai The Routledge Diaspora Studies Reader is a field-defining volume that presents an illuminating guide for established scholars and also those new to diaspora. Its accessible format offers a valuable resource, including suggestions for further reading and a glossary of key terms"--Provided by publisher.
Includes bibliographical references and index.
ENH
Parama
Keywords: Emigration and immigration; Immigrants -- Social conditions; Ethnology; Human geography; Transnationalism; Acculturation; Cultural pluralism